Clinical outcome following Doppler‐guided haemorrhoidal artery ligation: a systematic review. (24th June 2013) - Pucher, P. H.; Sodergren, M. H.; Lord, A. C.; Darzi, A.; Ziprin, P.
Abstract Aim Doppler‐guided haemorrhoidal artery ligation (DGHL) has experienced wider uptake and has recently received National Institute for Health and Clinical Excellence (NICE) approval in the UK. A systematic review of the literature was conducted to assess its safety and efficacy. Method This review was conducted in keeping with PRISMA guidelines. MEDLINE, EMBASE, Google Scholar and Cochrane Library databases were searched. Studies describing DGHL as a primary procedure and reporting clinical outcome were considered. Primary end‐points were recurrence and postoperative pain. Secondary end‐points included operation time, complications and reintervention rates. Studies were scored for quality with either Jadad score or NICE scoring guidelines. Results Twenty‐eight studies including 2904 patients were included in the final analysis. They were of poor overall quality. Recurrence ranged between 3% and 60% (pooled recurrence rate 17.5%), with the highest rates for grade IV haemorrhoids. Postoperative analgesia was required in 0–38% of patients. Overall postoperative complication rates were low, with an overall bleeding rate of 5% and an overall reintervention rate of 6.4%. The operation time ranged from 19 to 35 min. Conclusion DGHL is safe and efficacious with a low level of postoperative pain. It can be safely considered for primary treatment of grade II and III haemorrhoids.